Subcutaneous fatty acid composition of steers finished as weanlings or yearlings with and without growth promotants - Mapiye, Cletos (BioMed Central, 2013)
BACKGROUND: The current study evaluated the subcutaneous fatty acid (FA) composition of calf- and yearling-fed steers with or without growth promoting implants. Crossbred steers (n = 112; 267 ± 5.0 kg) of the same contemporary group were allocated to one of four production system and implant strategy based treatments in a completely randomized design with a 2 × 2 factorial arrangement of treatments. RESULTS: There were no interactions (P > 0.05) between production systems and growth promoting implants for the total and individual subcutaneous FA. Yearling as opposed to calf finishing reduced (P < 0.05) subcutaneous proportions of C20:3n-6, trans (t)12-18:1, C14:0, several minor cis-monounsaturated FA (c-MUFA; c9-14:1, c11-16:1, c11-18:1, c12-18:1, c13-18:1, c9-20:1 and c11-20:1), and increased (P < 0 .05) subcutaneous proportions of t11c15-18:2, total and individual branched-chain FA. Subcutaneous fat from steers implanted with growth promotants had higher (P < 0.05) proportions of total polyunsaturated FA (PUFA), total n-6 PUFA, C18:2n-6 and individual t-18:1 isomers (t6 to t10) compared to non-implanted steers. CONCLUSIONS: Overall, current findings show that production systems and growth promotants led to only minor differences in subcutaneous FA composition of beef steers.